Design and Implementation Monitoring System for The effects of Prolonged Sitting - Yulastri Yulastri; Aprinal Adila Asril; Era Madona; Roni Putra (JECCOM: International Journal of Electronics Engineering and Applied Science, 2023)
Workers spent more than two-thirds of their working hours sitting behind their desk. Almost all of them never put attention to good sitting position and caused health problems for themselves such as increasing the risk of hemorrhoids, heart disease, diabetes, obesity, joints damage, muscles and posture. The workers are not aware into account how long they had been sitting. Thus, one way to avoid health problems caused by long-term sitting is using a device which monitors body temperature, heart and muscle. In this study, the prototype is designed and implemented to monitor how long the worker had sit in their chair and the effect to their body. This system detected the temperature on the chair using temperature sensor, sensor ECG to heart detection placed on the finger and the sensor EMG to detect muscle is placed on the hand muscles. The information from the sensors are sent and saved to the database server and displayed through the website. The test results indicate that body weight and gender affect the speed of rise of body temperature which is measured on the seat cushions. Functional testing using the web interface successfully performed in displaying the results to the web interface sensor readings in real time and displays the results of the previous sensor readings.